Uma análise garantista da ilegitimidade da criminalização do usuário de drogas - Oliveira, Lucas Lopes (2015)
This paper addresses the issue of decriminalization of drug consumption across the criminal principles, a topic that will be discussed soon by the Supreme Court in Extraordinary Appeal No. 635659. In this sense, it tries to observe the possible incompatibility between the prohibition of consumption and the principles the penal system and the Federal Constitution. For this we use a penal criticism perspectives, which aims to rationalize the criminal law having as north the fundamental rights. Faced with the evils caused by prohibition in drugs users, work the hypothesis that the decriminalization of drugs would be a way of realization of the ideals of a penal criticism perspectives, avoiding the evils arising from the criminalization of drugs to the user. The method of procedure used is the legal and philosophical hermeneutics and the research technique is the bibliography (doctrinal concepts about penal criticism perspectives and on the issue of drugs) and documentary (jurisprudential research). Thus, if it is found such incompatibility must be considered, as illegitimate criminal prohibition of drugs consumption.